Inhibition of ceramide de novo synthesis by myriocin produces the double effect of reducing pathological inflammation and exerting antifungal activity against A. fumigatus airways infection - Caretti, Anna; Torelli, Riccardo; Perdoni, Federica; Falleni, Monica; Tosi, Delfina; Zulueta, Aida; Casas, Josefina; Sanguinetti, Maurizio; Ghidoni, Riccardo; Borghi, Elisa; Signorelli, Paola (Biochimica et biophysica acta, 2016)
Fungal infections develop in pulmonary chronic inflammatory diseases such as asthma, Chronic Obstructive Pulmonary Disease (COPD) and Cystic Fibrosis (CF). The available antifungal drugs may fail to eradicate fungal pathogens, that can invade the lungs and vessels and spread by systemic circulation taking advantage of defective lung immunity. An increased rate of sphingolipid de novo synthesis, leading to ceramide accumulation, was demonstrated in CF and COPD inflamed lungs. The inhibitor of sphingolipid synthesis myriocin reduces inflammation and ameliorates the response against bacterial airway infection in CF mice. Myriocin also inhibits sphingolipid synthesis in fungi and exerts a powerful fungistatic effect. We treated Aspergillus fumigatus infected airway epithelial cells with myriocin and we administered myriocin-loaded nanocarriers to A. fumigatus infected mice lung. We demonstrate here that de novo synthesized ceramide mediates the inflammatory response induced by A. fumigatus infection in airway epithelia. CF epithelial cells are chronically inflamed and defective in killing internalized conidia. Myriocin treatment reduced ceramide increase and inflammatory mediator release whereas it upregulated HO1 and NOD2, allowing the recovery of a functional killing of conidia in these cells. Myriocin-loaded nanocarriers, intratracheally administered to mice, significantly reduced both the inflammatory response induced by A. fumigatus pulmonary challenge and fungal lung invasion. We conclude that inhibition of sphingolipid synthesis can be envisaged as a dual anti-inflammatory and anti-fungal therapy in patients suffering from chronic lung inflammation with compromised immunity. Myriocin represents a powerful agent for inflammatory diseases and fungal infection. •A. fumigatus infection induces ceramide de novo synthesis and inflammation.•Myriocin reduces inflammatory mediators induced by A. fumigatus infection.•Myriocin corrects in Cystic Fibrosis defective killing of A. fumigatus.•Myriocin upregulates HO1 and NOD2 defensive pathways.•Myriocin significantly affects fungal lung invasion.